Localization of Magic-F1 Transgene, Involved in Muscular Hypertrophy, during Early Myogenesis. (10th December 2011) - Ronzoni, Flavio; Bongio, Matilde; Conte, Silvio; Vercesi, Luigi; Cassano, Marco; Tribioli, Carla; Galli, Daniela; Bellazzi, Riccardo; Magenes, Giovanni; Cusella De Angelis, Maria Gabriella; Sampaolesi, Maurilio
Abstract : We recently showed that Magic-F1 (Met-activating genetically improved chimeric factor 1), a human recombinant protein derived from hepatocyte growth factor/scatter factor (HGF/SF) induces muscle cell hypertrophy but not progenitor cell proliferation, both in vitro and in vivo . Here, we examined the temporal and spatial expression pattern of Magic-F1 in comparison with Pax3 (paired box gene 3) transcription factor during embryogenesis. Ranging from 9.5 to 17.5 dpc (days post coitum) mouse embryos were analyzed by in situ hybridization using whole mounts during early stages of development (9.5–10.5–11.5 dpc) and cryostat sections for later stages (11.5–13.5–15.5–17.5 dpc). We found that Magic-F1 is expressed in developing organs and tissues of mesenchymal origin, where Pax3 signal appears to be downregulated respect to the wt embryos. These data suggest that Magic-F1 could be responsible of muscular hypertrophy, cooperating with Pax3 signal pathway in skeletal muscle precursor cells.